Screening for antmacterial activities of melastoma malabathricum leaves extract against selected microorganism / Wan Nor Hamizah Wan Ismail - Wan Ismail, Wan Nor Hamizah (Faculty of Applied Sciences, 2017)
Melastoma malabathricum is a plant that has benefits in medicine. All parts of M malabathricum from root to shoot have potential to treat the diseases. The objectives of the study are to perform sequential extraction, to identify the secondary metabolites and to determine the antimicrobial activities against two bacteria which are Staphylococcus aureus and Pseudomonas aeruginosa. The solvents used for phytochemical screening test were hexane and methanol. Antimicrobial activity was investigated using disk diffusion method. The extracts were test with different concentration which 100 mg/ml, 80 mg/ml, 60 mg/ml, 40 mg/ml, and 20 mg/ml. The phytochemical analysis of hexane extracts showed the presence of flavonoid, phenol and tannins, while methanol extracts showed the presence of glycoside and tannins. Different concentrations of crude extract show significant difference (P ≤ 0.05). Methanol leaves extract at concentration of 100 mg/ml showed the highest antibacterial activity against S. aureus and P. aeruginosa with zone of inhibition of 16 mm and 26 mm respectively. Thus, it indicate that methanol leaves extract contain high components related to antibacterial activity. As a conclusion M malabathricum methanol leaves extract potentially can be used against gram positive and negative bacteria.